Nanoindentation and micromechanical testing of iron-chromium alloys implanted with iron ions - Halliday, F; Armstrong, D; Murphy, J; Roberts, S (2009)
The mechanical properties of Fe-Cr alloys were investigated in as-grown and in post-ion-implanted conditions. Sets of specimens were produced using dual implantations of Fe+ ions to give 1μm deep damaged layers with average damage levels of 0.35 displacements per atom and 5.33 displacements per atom. Nanoindentation was used to measure hardness as a function of depth and showed that implanted material had a higher hardness than unimplanted material. Additionally, micron-scale cantilevers were fabricated from the ion-damaged surface of the material and were tested using a nanoindenter for AFM-imaging and loading. The mechanical properties deduced from the controlled loading of these cantilevers pertain only to radiation-damaged material, and for the high-dose material show significant changes in Young's modulus, yield stress and work-hardening. © 2009 Trans Tech Publications, Switzerland.